Ea recombinational hot spot in the mouse major histocompatibility complex maps to the fourth intron of the Ea gene. - Khambata, S; Mody, J; Modzelewski, A; Heine, D; Passmore, H C (Genome Research, 1996)
The majority of recombination events detected within the mouse major histocompatibility complex (MHC) fall into regions of limited physical distance known as hot spots of meiotic recombination. The hot spot associated with the Ea gene appears to be active only in the presence of the p allele carried by the intra-MHC recombinant strain BIO.F(13R). To study the frequency, regulation, and haplotype specificity of recombination at the Ea hot spot, progeny from three different backcrosses involving BIO.F(13R) were screened for recombination events across the MHC using DNA microsatellite markers. Screening of a total of 750 backcross progeny permitted the identification of seven recombinants within the Ea gene. Using restriction site polymorphisms, and sequence-based nucleotide polymorphisms, the recombination breakpoints in all seven Ea recombinants were mapped to two adjacent segments of 71 bp and 346 bp in intron 4 of the Ea gene.